Genetic polymorphism in HSPB6 gene and their association with heat tolerance in Sahiwal cattle - RAKESH KUMAR; ISHWAR DAYAL GUPTA; ARCHANA VERMA; RAGINI KUMARI; NISHANT VERMA; RAJIB DEB; RAMENDRA DAS; M V CHAUDHARI (Indian Journal of Animal Sciences, 2022)
Heat shock proteins (HSPs) are known to modulate cellular response during summer stress in dairy cattle. Among different classes of HSPs, heat shock protein 20 (HSPB6) is a member of the small HSP family protein, the role of which has not been fully characterized in the context of heat stress in cattle. This study identified single nucleotide polymorphisms (SNPs) in the HSPB6 gene in Sahiwal cattle and their associations with heat tolerance traits (RR, RT and HTC). Three SNPs (SNP 1-3) were reported, which included two transitions, viz. SNP1-g.436G>A (Intron 1) and SNP2-g.2152A>G (3′-UTR) and one transversion, viz. SNP3-g.2417A>T (3′-UTR). The association analysis revealed that SNPs loci, viz. SNP1-g.436G>A and SNP2-g.2152A>G were significantly associated with heat tolerance traits. The GG genotype of SNP2-g.2152A>G was significantly associated with heat tolerance traits in Sahiwal cattle. The association analysis of four available haplotypes, viz. Hap1 (GGA), Hap2 (AAA), Hap3 (GAA), and Hap4 (AAT) of HSPB6 gene with heat tolerance traits did not differ significantly with any haplotype in Sahiwal cattle. This study provides the first association analyses between the SNPs of HSPB6 gene and heat tolerance traits in Sahiwal cattle, which could be used as effective SNP markers in genetic selection for heat tolerance in cattle breeding programs.